First-trimester miscarriage rate decreases with hydralazine therapy in pregnancies with early uterine vascular insufficiency: a cohort study. (12th December 2022) - Leible, Sergio; Canals, Andrea; Walton, Roderick; Mitelman, Gabriel; Castiglione, Angelo; Biron, Miguel; Faundez, Rosana; Sepulveda, Waldo
Abstract: Background: Miscarriage is the most frequent cause of pregnancy loss, affecting 15–20% of clinically recognized pregnancies. Early uterine vascular insufficiency (EUVI), defined as abnormal uterine artery (UA) Doppler impedance indices in early pregnancy, is present in two-thirds of pregnancies ending in miscarriage after embryonic cardiac activity has been detected. There is currently no available therapy for reducing the risk of miscarriage in these cases. Objective: To determine whether vasodilator therapy with hydralazine can reduce abnormally high UA impedance indices and miscarriage rates in pregnancies with EUVI when administered from before 9 weeks' gestation until completing 13 weeks' gestation. Methods: A total of 253 consecutive singleton pregnancies with a live embryo and scanned before 9 weeks' gestation were included in the study. Ninety-two pregnancies (36.3%) were classified as having EUVI. Hydralazine was administered in daily doses of 50 mg, starting 24–36 h after the initial diagnosis of EUVI and continuing throughout the first trimester. The miscarriage rate in the hydralazine-treated EUVI group was compared with the one observed in our previously reported untreated cohort and the pregnancies with EUVI that declined treatment with hydralazine. Results: The miscarriage rate among the hydralazine-treated EUVI group was significantly lower than the previously reported untreated cohort (7.8% versus 26.2%, p  = .003; odds ratio (OR) = 4.3, 95% confidence interval (CI) = 1.6–11.9). In 15 untreated pregnancies with EUVI, the miscarriage rate was similar to that of the previously reported untreated cohort (26.7% versus 26.2%; p  = .603) and higher than the hydralazine-treated group (26.7% versus 7.8%, p  = .05; OR = 4.4, 95% CI = 1.1–18.2). Conclusions: Hydralazine therapy in pregnancies with EUVI was associated with a significant decrease in the rate of miscarriage. We suggest a sequence of events leading to a higher risk of miscarriage in pregnancies with EUVI and propose a potential mechanism through which hydralazine may reduce this risk.